The utility and safety of linear endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in the paediatric population. Issue 4 (29th April 2020) - Al-Najjar, Haider; Breen, Ronan; Santis, George; Narayan, Omendra
Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in adults is an essential tool for investigating mediastinal and hilar lymphadenopathy. It is now integral to the diagnostic and staging algorithm for lung cancer [1], as well as the diagnosis of other malignancies, lymphoma and non-malignant granulomatous conditions, such as sarcoidosis and tuberculosis. The comparable diagnostic yield, along with decreased complications, has reduced the requirement for previously standard surgical biopsy sampling [2, 3]. This first European case series demonstrates that EBUS-TBNA, well established in the diagnosis of mediastinal and hilar adenopathy in adults, is a safe and useful diagnostic alternative to invasive surgical biopsy in the paediatric population http://bit.ly/389Uvq4